The Autobiography of a Legend: Sachin Tendulkar’s Playing it My Way (Journal of Advances and Scholarly Researches in Allied Education, 2025)
“I had always dreamed of playing cricket for India. Getting an opportunity to fulfil my dream at such an early age was indeed very special.”An autobiography is a self-written account of a person’s life, reflecting their experiences, thoughts, and perspectives."With its candid and introspective narrative, 'Playing It My Way' provides a unique perspective on Tendulkar's life and career, highlighting his triumphs, setbacks, and lessons learned. The book is a treasured trove of insights into the mind of a champion, making it a must-read for anyone looking to understand the dedication and hard work that goes into achieving greatness in sports and beyond." Co-written with Boria Majumdar, “Playing It My Way” is a must-read for cricket fans and sports enthusiasts, offering a fascinating glimpse into the life of a cricket legend. The book is an inspiring and engaging account of Tendulkar’s journey, making it a compelling read for anyone interested in sports and personal development. “The book is a captivating account of Tendulkar’s life, showcasing his dedication, perseverance, and passion for cricket. Through his story, readers gain a deeper understanding of the cricket legend’s experiences, both on and off the field. ‘Playing It My Way’ is an inspiring and engaging read, offering valuable insights into the life of one of cricket’s greatest players.” One of the most positive influences that have been specified by Sachin Tendulkar on the Indian society is that the maintenance of humble nature towards everybody is highly necessary which has always been incorporated in his conduct. In the autobiography, he has clearly mentioned that he was always prominent and dreamed of playing cricket for the Indian cricket team and when he eventually came across the opportunity, he gave his best. Sachin Tendulkar is one of the most loved and glorified cricket personalities in India.